Assessment of Future Remnant Liver Function Using Hepatobiliary Scintigraphy in Patients Undergoing Major Liver Resection - de Graaf, Wilmar (Springer-Verlag, 2009)
BACKGROUND: (99m)Tc-mebrofenin hepatobiliary scintigraphy (HBS) was used as a quantitative method to evaluate liver function. The aim of this study was to compare future remnant liver function assessed by (99m)Tc-mebrofenin hepatobiliary scintigraphy with future remnant liver volume in the prediction of liver failure after major liver resection. METHODS: Computed tomography (CT) volumetry and (99m)Tc-mebrofenin hepatobiliary scintigraphy were performed prior to major resection in 55 high-risk patients, including 30 patients with parenchymal liver disease. Liver volume was expressed as percentage of total liver volume or as standardized future remnant liver volume. Receiver operating characteristic (ROC) curve analysis was performed to identify a cutoff value for future remnant liver function in predicting postoperative liver failure. RESULTS: Postoperative liver failure occurred in nine patients. A liver function cutoff value of 2.69%/min/m(2) was calculated by ROC curve analysis. (99m)Tc-mebrofenin hepatobiliary scintigraphy demonstrated better sensitivity, specificity, and positive and negative predictive value compared to future remnant liver volume. Using (99m)Tc-mebrofenin hepatobiliary scintigraphy, one cutoff value suffices in both compromised and noncompromised patients. CONCLUSION: Preoperative (99m)Tc-mebrofenin hepatobiliary scintigraphy is a valuable technique to estimate the risk of postoperative liver failure. Especially in patients with uncertain quality of the liver parenchyma, (99m)Tc-mebrofenin HBS proved of more value than CT volumetry.